2021
DOI: 10.1007/s00431-021-04344-0
|View full text |Cite
|
Sign up to set email alerts
|

Cough and cold medicine prescription rates can be significantly reduced by active intervention

Abstract: Our aim was to construct and test an intervention programme to eradicate cough and cold medicine (CCM) prescriptions for children treated in a nationwide healthcare service company. The study was carried out in the largest private healthcare service company in Finland with a centralised electronic health record system allowing for real-time, doctor-specific practice monitoring. The step-by-step intervention consisted of company-level dissemination of educational materials to doctors and families, educational s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 25 publications
(20 reference statements)
2
22
0
Order By: Relevance
“…The participants diagnosed CAP in 301 children who were treated with antibiotics, and 94.1% of patients over age 5 years received antibiotics in accordance with the guidelines, compared with 78.6% in controls. The nationwide electronic health record system used by all doctors of the present study provides a suitable template for doctor‐specific education and feedbacks containing real‐time clinical data, including data on prescriptions, as was successfully used to reduce cough medicine prescriptions for children 24,25 . Based on our results, active interventions should not only target the use of appropriate therapy but also improving differential diagnosis of LRTIs in children.…”
Section: Discussionmentioning
confidence: 87%
“…The participants diagnosed CAP in 301 children who were treated with antibiotics, and 94.1% of patients over age 5 years received antibiotics in accordance with the guidelines, compared with 78.6% in controls. The nationwide electronic health record system used by all doctors of the present study provides a suitable template for doctor‐specific education and feedbacks containing real‐time clinical data, including data on prescriptions, as was successfully used to reduce cough medicine prescriptions for children 24,25 . Based on our results, active interventions should not only target the use of appropriate therapy but also improving differential diagnosis of LRTIs in children.…”
Section: Discussionmentioning
confidence: 87%
“…The authors of one Finnish study constructed, and tested, an intervention programme to reduce prescriptions for cough and cold medication. The cohort comprised children who were treated by a nationwide healthcare service company that used a centralised EHR that enabled it to monitor the clinical practices of specific doctors in real time 10 …”
mentioning
confidence: 99%
“…The total cost of the four‐year intervention for the company was about the same as the amount the parents spent on cough and cold medication during the last year. The study showed that a nationwide systematic intervention to reduce such prescriptions was feasible and only required modest financial investments and an online EHR system with coded data 10 …”
mentioning
confidence: 99%
See 2 more Smart Citations